ENVIRONMENTAL EVOLUTION OF THE LONGARINI AND CUBA LAGOONS (SOUTHEASTERN SICILY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1997)
The Longarini and Cuba lagoons are the largest westlands in a system of lagoons located inland of the Ambra Coast in southeastern Sicily.A reconstruction of their evolution througt a comparative study of textural, compositional and faunal data, showed facies of a lagoonal system influenced differently and in varying degrees by rivers and sea. The oldest layers are made of lagoonal pelitic sediments containing faunal assemblages (mixed biocenoses) referable to the zonal classification of the paralic environment proposed by Guelorget & Perthuisot (1983). In the more recent layers an environmental change is recorded,showing an increase in lagoonal characteristics and a decrease in "mixed" biocenoses, due to a greater input of solid materials from the adjacent hydrographic basin.